Ministry of Health and Population Decree No. 204 of the Year 2015 Regarding the Food Additives Authorized to be used in Food Industry = قرار وزير الصحة والسكان رقم 204 لسنة 2015 بشأن الإضافات الغذائية المصرح باستخدامها فى الصناعات الغذائية - The Middle East Library for Economic Services (The Middle East Library for Economic Services, 2025)
English & Arabic